Psychometric validation of the desire thinking questionnaire in a Turkish adolescent sample: Associations with internet gaming disorder. (February 2022) - Aydın, O.; Ünal-Aydın, P.; Caselli, G.; Kolubinski, D.C.; Marino, C.; Spada, M.M.
Highlights: The Desire Thinking Questionnaire was validated in Turkish adolescent sample. Desire thinking is associated with Internet Gaming Disorder among adolescents. Suspending desire thinking may alleviate the symptoms of Internet Gaming Disorder. Abstract: Background: Desire thinking is a conscious and voluntary cognitive process that consists of perseverative focus on information, memories, and prefiguration of images related to a desired target. The Desire Thinking Questionnaire (DTQ) is acknowledged as a reliable and valid tool to measure desire thinking in both adults and adolescents. The aim of the present study was to examine the psychometric properties of the DTQ in Turkish adolescent sample. Methods: A convenience sample of 200 adolescents completed the Turkish version of the DTQ (DTQ-T) and an Exploratory Factor Analysis (EFA) was performed. Subsequently, a convenience sample of 701 adolescents completed the DTQ-T and a battery of questionnaires assessing personality traits, affect, boredom, impulsivity, and Internet Gaming Disorder (IGD). A Confirmatory Factor Analysis (CFA) was performed on the DTQ-T and validity was determined by examining correlations with other measures. Results: A 9-item two-factor structure was observed in the EFA. An 8-item two-factor structure was established in the CFA. Results demonstrated that the DTQ-T yields adequate levels of reliability and concurrent validity. Additionally, an examination of incremental validity showed that DTQ-T significantly predicted IGD when controlling for personality traits, affect, boredom, and impulsivity. Conclusions: The 8-item DTQ-T was found to be a reliable and valid measure of desire thinking among Turkish adolescents. Desire thinking may be a feasible target for mental health workers to alleviate the symptoms of IGD.